Parents’ Knowledge of ’Tarak’ Breastfeeding Mothers in Indonesia - Mardhika, Amellia; Sulistyono, Agus; Cahyati, Elok Nur; Mei Tyas, Anestasia Pangestu; Sulpat, Emuliana; Fadliyah, Lailatul (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the relationship between the level of knowledge of parents about ‘tarak’ on eating patterns in breastfeeding mothers. Methods: This study uses a descriptive correlational design with a cross-sectional approach. The sample in this study was determined by the krejcie and morgan sample size table as many as 99 pairs of breastfeeding mothers and mother in-laws were selected using a purposive sampling technique in East Java, Indonesia. The Spearman test was performed in the final test for knowledge of parents about ‘tarak’ (independent variable) and eating patterns in breastfeeding mothers (dependent variable). Results: The results informed that there was no relationship between the level of parental knowledge about ‘tarak’ on eating patterns in nursing mothers, with p = 0.154. Conclusion: There was no relationship between knowledge of ‘tarak’ and the eating pattern of breastfeeding mothers. Although the mother’s diet is not influenced by knowledge of ‘tarak’, it is still necessary to educate parents about ‘tarak’ and the proper diet for breastfeeding mothers to prevent misinformation. So that breastfeeding mothers can increase nutritional intake during breastfeeding. Keywords: Breastfeeding, Eating, Diet, Nutritional, Tarak